2022
DOI: 10.31893/jabb.22040
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the melatonin receptor 1A (MTNR1A) gene do not affect sexual activity, plasma testosterone concentrations or testicular characteristics of 8-month-old ram-lambs born in autumn

Abstract: Thirty-nine autumn-born ram-lambs were used to study whether polymorphisms of the melatonin receptor 1A (MTNR1A) gene influence some reproductive parameters of Oct-born ram-lambs at 8 months of age. Animals were genotyped for their RsaI (CC, n=24; CT, n=6; TT, n=9) and Mn1I (GG, n=27; GA, n=6; AA, n=6) allelic variants of the MTNR1A gene. Liveweight (LW) was recorded bi-weekly until Jun, and scrotal perimeter (SP) was recorded once per month. From mid-Jan, blood samples were collected weekly to measure plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous research by our group has shown that the T/T or the G/G genotype for the RsaI and MnlI polymorphisms, respectively, has a positive effect on the sexual performance of young and adult Rasa Aragonesa rams (Abecia et al 2020). Specifically, autumn-born ram lambs that carried the T/T or the G/G genotype were considerably younger at first mounting, while adult T/T and G/G rams exhibited a more intense reproductive behaviour than rams without these genotypes (Abecia et al 2020) although it was not associated with differences in social dominance (Abecia et al 2022). Moreover, the polymorphisms of the MTNR1A gene of rams seem to affect field fertility after artificial insemination (AI) depending on season (Abecia et al 2023), although the reason for these differences remains unknown.…”
Section: Pe˜mentioning
confidence: 95%
“…Previous research by our group has shown that the T/T or the G/G genotype for the RsaI and MnlI polymorphisms, respectively, has a positive effect on the sexual performance of young and adult Rasa Aragonesa rams (Abecia et al 2020). Specifically, autumn-born ram lambs that carried the T/T or the G/G genotype were considerably younger at first mounting, while adult T/T and G/G rams exhibited a more intense reproductive behaviour than rams without these genotypes (Abecia et al 2020) although it was not associated with differences in social dominance (Abecia et al 2022). Moreover, the polymorphisms of the MTNR1A gene of rams seem to affect field fertility after artificial insemination (AI) depending on season (Abecia et al 2023), although the reason for these differences remains unknown.…”
Section: Pe˜mentioning
confidence: 95%
“… 19 This includes the nuclei that are responsible for reproduction. 20 Preceding studies have revealed that the polymorphisms in the MTNR1A gene sequence have an effect on the ability of Rasa Aragonesa rams to reproduce both when they are young and when they are adults. 6 In particular, the T/T or G/G genotype was shown to be connected with earlier ram-lamb mating activity, and adult rams that carried the T/T or G/G genotype exhibited the highest reproductive behavior in the spring.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In particular, the T/T or G/G genotype was shown to be connected with earlier ram-lamb mating activity, and adult rams that carried the T/T or G/G genotype exhibited the highest reproductive behavior in the spring. 20 …”
Section: Introductionmentioning
confidence: 99%